2021
DOI: 10.1007/s43576-021-00022-1
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence Victimization Among Adolescent Girls in the American Rural South

Abstract: Research has shown that girls in rural contexts are more likely to experience dating violence victimization than peers in urban or suburban ones. Yet, little research has been carried out on rural adolescent girls in regard to the outcomes of such dating violence and the role of parenting. The current study tested the link between dating violence victimization (both general and sexual violence victimization) and internalizing problems (depression, anxiety, and low self-esteem), and whether maternal peer approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A review of the literature suggests that this group may be even more underserved than their adult counterparts (Finkelhor and Ormrod 2001;. Furthermore, studies have revealed a higher risk of victimization among rural adolescent girls than their urban counterparts (Martz et al 2016;Musu-Gillette et al 2018;Peek-Asa et al 2011;Liu et al 2021).…”
Section: Reporting Victimization To Policementioning
confidence: 99%
“…A review of the literature suggests that this group may be even more underserved than their adult counterparts (Finkelhor and Ormrod 2001;. Furthermore, studies have revealed a higher risk of victimization among rural adolescent girls than their urban counterparts (Martz et al 2016;Musu-Gillette et al 2018;Peek-Asa et al 2011;Liu et al 2021).…”
Section: Reporting Victimization To Policementioning
confidence: 99%
“…A lthough understanding the nature, risk factors and consequences of adolescent dating violence has become more complete and rigorous over the past decades, gaps remain in knowledge of violence disclosure and help-seeking, a crucial component to preventing further victimization and perpetration and minimizing harm. Research is scarce on whether and how disclosure of dating abuse evolves among developing adolescents, especially among youth in rural areas (Liu et al, 2021). Despite substantial theoretical justification, studies focusing on intentions to disclose relationship abuse rarely account for heterogeneity within adolescent populations, potentially obscuring important differential effects (cf.…”
mentioning
confidence: 99%